Implementasi Metode Kompresi Gambar dari Node Sensor ke Node Server untuk Meningkatkan Efisiensi Waktu Pengiriman pada Jaringan 6LoWPAN - Mohammad Harits; Adhitya Bhawiyuga; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Wireless Sensor Network has been able to be applied in agriculture to monitor the condition of agricultural land, namely regarding the humidity, pH, and temperature of the soil. However, this monitoring process cannot take pictures on the location because Wireless Sensor Network has the disadvantage of not being able to send large datas. To solve this problem, you can use a large capacity communication module so that more data is sent and also use the compression method for data to reduce the size of data before being sent. The communication module used in this study is 6LoWPAN. 6LoWPAN was chosen because it has advantages in terms of transmission capacity, range and has a low power consumption. There are 2 compression methods used, namely the DCT algorithm which is used to reduce interpixel redundancy and RLE to condense the results of the DCT algorithm so it can be smaller. The results obtained after testing are that the application of the compression method can save image size by around 24% from the size of the original image and reduce the total package sent by about 77% of the original packet. Delivery performance using the compression method has the advantage of sending time but decreases the success rate and increases average delay when sending image data.